MENINGKATKAN KEKAYAAN MUFRODAT SISWA MELALUI METODE HYPNOTEACHING - Almanna Wassalwa; Agung Wijaksono (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
The research objective is to increase the wealth of mufrodat through hypnoteaching methods. The research subjects were all fifth grade students of MI Miftahun Najah Banyuputih Situbondo in the 2016/2017 Academic Year. Researchers used data collection instruments in the form of observation formats, question sheets, field notes, and interview guidelines. The research method is classroom action research. Data analysis techniques are planning, acting, observing and reflecting. The results of the study are: 1) The average memorization of students' mufrodat in the pre cycle before receiving hypnoteaching learning method treatment gets an average of 65.38. The smallest value is 55 and the highest value is 80. With the Minimal Completeness Criteria reference of 70, the number of students who get a score equal to or above the Minimal Completeness Criteria is 23% while students who have not reached the Minimal Completeness Criteria is 77%. 2) The average memorization of students' mufrodat in the first cycle after applying hypnoteaching learning method got an average of 72.3. The smallest value is 55 and the highest value is 80. With the Minimal Completeness Criteria reference of 70, the number of students who score equal to or above the Minimal Completeness Criteria is 61.5% while students who have not reached the Minimal Completeness Criteria is 38.5%. 3) The average memorization of students' mufrodat in the second cycle gets an average of 90. The smallest value is 75 and the highest score is 100. With a Minimal Completeness Criteria reference of 70, the number of students who score equal to or above the Minimal Completeness Criteria is 92.3% while students who have not yet reached Minimal Completeness Criteria is 7.7%. 4) The use of hypnoteaching method can increase the wealth of mufrodat of fifth grade students of MI Miftahun Najah Banyuputih Situbondo in 2016/2017 Academic Year.